Chemical and biological air pollutants, as parameters of complex air quality indices - Eötvös, Tekal; Makra, László (Acta Geographica Debrecina Landscape & Environment series, 2007)
Human health is essentially influenced by air quality. Atmospheric air in residential areas contains many pollutants. The monitoring and the plain publishing of the measured values are important both for the authorities and the public. Air quality is often characterized by constructing air quality indices, and these indices are used to inform the public. The construction of an advanced air quality index is usually done by averaging the measured data usually in time and space; hereby important aspects of the data can be lost. All known indices contain only chemical pollutants, while certain biological pollutants can enhance the effects of the chemical pollutants and vice versa. In this paper we discuss the importance of integrating biological pollutants into air quality indices. In order to increase efficacy of these indices to the civil society we aim to introduce geographic information system (GIS) methods into publishing air quality information.